The Government Policy in Realizing the Sustainability of Labeobarbus Douronensis "Dewa Fish" - Suwari Akhmaddhian; Erga Yuhandra; Ressa Siti Nurhasanah (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
The present study aims to identify the regulations on the conservation of natural resources and their impact on community welfare. This study applied an empirical juridical approach. The primary and secondary data used in this study were collected through interviews, observation, and literature study. As results, it can be identified that fish conservation in Indonesia is regulated by various laws and regulations, including Law on Fisheries, Law on Environmental Protection and Management, Government Regulation on Conservation of Fishery Resources, Government Regulation on Fish Farming, Regulation of the Minister of Environment and Forestry on Recognition and Protection of Local Wisdom in the Management of Natural Resources and Environment, Regional Regulation on Implementation of Tourism, Regional Regulation on Preservation of Local Culture, as well as Regional Regulation on Conservation of Birds and Fish which give the authority to Kuningan District Regional Government in the conservation of ‘god fish’. The conservation of ‘god fish’ based on local wisdom of ‘pamali’ is in the form of prohibition on damaging the spring in Cibulan Tourist Attraction and prohibition on disturbing ‘god fish’. To conclude with, the conservation of natural resources, especially ‘god fish’, through water-based tourism management has positive implications for community welfare.